"Evidence": Garth Risk Hallberg's City on Fire, the Gutenberg Parenthesis, and Generation X at Midlife. Issue 5 (20th October 2018) - Glover, Brian
ABSTRACT: Though Garth Risk Hallberg's City on Fire has been read as a historical novel about the 1970s, this article argues that it is better understood as a meditation on the arrival of digital communications technologies around the turn of the millennium, as well as the analog technologies that were then superseded (chief among them, the novel). It traces the post-millennial transformation of Generation X as a cultural phenomenon and places Hallberg in relation to other novelists of that generation. City on Fire is also considered in relation to early-twenty-first-century memorial culture and the transformations of both the punk subculture and the physical format of the book in response to the Internet. Hallberg has created both a guide for the last survivors of the analog world and a monument for those who come after them.